EFL LEARNERS’ PHONOLOGICAL INTERFERENCE OF ENGLISH ARTICULATION - Ambalegin Ambalegin; Fasaaro Hulu (Universitas Putera Batam, 2019)
This research investigated the mispronunciation of Putera Batam University EFL learners by adapting the standard of Received Pronunciation (RP) and the factors of English vowels and consonants mispronunciation. This descriptive qualitative research applied observational method with participatory technique in collecting data, and articulatory identity method in analyzing the data. The English mispronunciation was found in the EFL learners’ English pronunciation. The consonant sounds /ð/, /θ/, /th/, /z/, /r/, /ʃ/, /ʧ/, /ʤ/, /nj/, and consonant-closed syllable sound of /k/ were pronounced incorrectly. The consonant sound /ð/ was pronounced as /d/, /θ/ as /t/, /th/ as /t/, /z/as /ɉ/, /r/ as /ɾ/, /ʃ/ as /s/, /ʧ/ as /s/, /ʤ/ as /d/, and /nj/ is pronounced as /ɲ/. Consonant-closed syllable sound of /k/ is articulated as /Ɂ/. The vowel sounds /ə/ and /æ/ were pronounced incorrectly as /e/ and the diphthong sound /eɪ/ were pronounced incorrectly as /e/. These mispronunciation phenomena were caused by some factors based on their background. The factors were; the mother tongue interference (native language), the differences between Indonesian and English sound systems (phonetic ability), the educational background, and the environmental background (amount of exposure).